Imported Goods Delivery Service Administration Procedures at PT Tritunggal Agung Sejahtera Jakarta - Yulia Ayu Cahyani Waworuntu; Hieronimus Erwin Indrawan; Yudha Febri al Paksi; Ananto Krisna Wardhana (Institute of Computer Science (IOCS), 2021)
PT. Tritunggal Agung Sejahtera is a company engaged in export and import goods shipping services. Because of the current shipping service much needed by the wider community and also made easy by ordering goods through social media, then PT Tritunggal Agung Sejahtera guarantee the best service at all times when sending goods by coordinating and monitoring all shipments of goods are assisted by the latest computer systems. Data collection methods in the preparation of the final project is a method of obsevation, interviews, and analysis methods library study of qualitative analysis method. PT Tritunggal Agung Sejahtera can be called a trucking company because it sends shipments of imported goods by focusing on shipping goods via land by renting containers or trucks in carrying out its services. PT Tritunggal Agung Sejahtera using a computerized administration system which is the Cube application as a support for the administrative process of sending imported goods, such as inputting documents that have been received by customers until the payment of bills.